Army Jayapura: Komunitas Penggemar K-Pop di Papua - Delvia Insyowi Sroyer; Simon Abdi K. Frank; Hanro Y. Lekitoo (Universitas Cenderawasih, 2022)
The purpose of this study is to find out the history of Jayapura Army community as fond of K-Pop culture on the of the Army community in Jayapura. The method used by author in this study is a descriptive qualitative research type. To obtain objective data, the author uses interview research techniques, observatios, and documentation. The author examines directly related to what is happening in the field, then the author describes what is seen, heard and collected according to the data needed in this research topic. In this study recording aids in the form of mobile phones and field notes were also used. The location of this research was in Abepura, Kota Baru Ward, Abepura District, Jayapura City, Papua Province. The informant technique used by the researcher is purposive sampling. The purpose of this study is to find out the history of Jayapura Army community as fond of K-Pop culture on the of the Army community in Jayapura. The results of this study indicate that K-Pop culture, one of which is boyband BTS has entered Abepura, Jayapura Papua precisely in the Army Jayapura community in 2016 and BTS is veryinfluential and has appositive inpact on the Army Jayapura to do positive things rafter than negative things.